1966
DOI: 10.1177/002072096600400402
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded R–C Networks and Phase-shift Oscillators

Abstract: This article briefly describes the salient features of the simple three section C–R phase-shift oscillator which is met quite early in electronics laboratory courses. The frequency of operation and the gain required for oscillation are shown to depend on the output impedance of the amplifier which feeds the C–R network. By using a directly coupled cathode follower, the C–R network can be driven under almost ideal conditions where the C–R network determines the frequency and gain requirement. A simple and rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For the thorium chain, the important alpha emitters are 216 Po (6.8 MeV alpha) and 212 Po (8.8 MeV alpha), and for the uranium chain are 218 Po (6.0 MeV alpha), 214 Po (7.7 MeV alpha), and 210 Po (5.3 MeV alpha). Detailed information including tables of (α, n) yields from light nuclides as a function of alpha energy are given by References (137,138).…”
Section: Neutrons From Uranium and Thorium In Rockmentioning
confidence: 99%
“…For the thorium chain, the important alpha emitters are 216 Po (6.8 MeV alpha) and 212 Po (8.8 MeV alpha), and for the uranium chain are 218 Po (6.0 MeV alpha), 214 Po (7.7 MeV alpha), and 210 Po (5.3 MeV alpha). Detailed information including tables of (α, n) yields from light nuclides as a function of alpha energy are given by References (137,138).…”
Section: Neutrons From Uranium and Thorium In Rockmentioning
confidence: 99%
“…Our calculations with SOURCES show that spontaneous fission dominates the neutron production from uranium in iron. We compared our results for a total neutron yield from U and Th in iron and stainless steel with a calculation carried out by Heaton [26] for iron on the basis of the measurements by West and Sherwood [27]. We found that for equal contamination levels of U and Th, Heaton's yield for iron is 57% higher than our result for iron.…”
Section: Neutrons From Detector Componentsmentioning
confidence: 57%
“…We can interpret this difference as an estimate for the systematic uncertainty in our calculations. Unfortunately, the calculations of Heaton [26] cannot be used to generate recoil spectra since they do not contain information about neutron energies and the cross-sections of (α,n) reactions are not available from the measurements quoted above.…”
Section: Neutrons From Detector Componentsmentioning
confidence: 99%